Plasticity of temporal information processing in the primary auditory cortex - Kilgard, Michael P. (1998)
Neurons in the rat primary auditory cortex (A1) generally cannot respond to tone sequences faster than 12 pulses per second (pps). To test whether experience can modify this maximum following rate in adult rats, trains of brief tones with random carrier frequency but fixed repetition rate were paired with electrical stimulation of the nucleus basalis (NB) 300 to 400 times per day for 20–25 days. Pairing NB stimulation with 5-pps stimuli markedly decreased the cortical response to rapidly presented stimuli, whereas pairing with 15-pps stimuli significantly increased the maximum cortical following rate. In contrast, pairing with fixed carrier frequency 15-pps trains did not significantly increase the mean maximum following rate. Thus this protocol elicits extensive cortical remodeling of temporal response properties and demonstrates that simple differences in spectral and temporal features of the sensory input can drive very different cortical reorganizations.